2022
DOI: 10.1107/s2052252522005309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of modelling disorder on Hirshfeld atom refinement results of an organo-gold(I) compound

Abstract: Details of the validation of disorder modelling with Hirshfeld atom refinement (HAR) for a previously investigated organo-gold(I) compound are presented here. The impact of refining disorder on HAR results is discussed using an analysis of the differences of dynamic structure factors. These dynamic structure factor differences are calculated from thermally smeared quantum mechanical electron densities based on wavefunctions that include or exclude electron correlation and relativistic effects. When disorder is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Including electron correlation effects is necessary to avoid non-positive defined thermal parameters [76]. Moreover, it has been shown that the distributions of the dynamic structure factors showing the effects of electron correlation and treatment of H-atom ADPs have similar shapes [135], which supports the observation made by Malaspina et al [76]. In the context of data quality, it is essential to ensure that the data used for these studies are of high quality and accurately represent the experimental observations.…”
Section: Challengesmentioning
confidence: 55%
“…Including electron correlation effects is necessary to avoid non-positive defined thermal parameters [76]. Moreover, it has been shown that the distributions of the dynamic structure factors showing the effects of electron correlation and treatment of H-atom ADPs have similar shapes [135], which supports the observation made by Malaspina et al [76]. In the context of data quality, it is essential to ensure that the data used for these studies are of high quality and accurately represent the experimental observations.…”
Section: Challengesmentioning
confidence: 55%
“…Supramolecular chemistry poses some specific challenges to these approaches, in particular the size and complexity of their structures, data quality issues, as well as the presence of heavy elements and disorder. However, since the first report of diffraction data treated with this technique, 118 Hirshfeld Atom Refinement has become increasingly popular 119–121 and more easily accessible 122 with improvements in IT, molecular modelling and DFT (in particular) in recent years. As such, it is inevitable that these integrated calculation methods will become increasingly relevant in the years to come.…”
Section: The Future Of Diffraction Techniquesmentioning
confidence: 99%
“…In particular, elements with Z > 35 exhibit large residual electron-density values after refinement using both spherical and non-spherical electrondensity models. Examples exhibiting the structured appearance of these residual electron-density distributions, even after non-spherical refinements, were presented in recent studies for Hg, Os or Au (Malaspina et al, 2019;Pawle ˛dzio et al, 2021Pawle ˛dzio et al, , 2022. The increasing threshold for residual electron-density values of structures containing heavier elements before a warning is triggered during data validation procedures by the IUCr CheckCIF procedure (https://checkcif.iucr.org/) tries to address these growing discrepancies during structure validation.…”
Section: Introductionmentioning
confidence: 99%